Feasibility and long-term outcomes of leadless pacemaker implant after transvenous lead extraction. (19th May 2022) - Parollo, M; Barletta, V; Mazzocchetti, L; Gentile, F; De Lucia, R; Viani, S; Segreti, L; Di Cori, A; Zucchelli, G; Bongiorni, MG
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Infections and malfunction are major indications to transvenous lead extraction. Managing extracted patients represents a clinical and interventional challenge, since this population may be at higher risk for mechanical, vascular or infective complications. The use of leadless pacing systems has been described as a potentially useful technology that could tackle the obstacles that affect this peculiar population. The study aimed to investigate feasibility and long-term outcomes of M-TPS implant in a specific patient population, like post transvenous lead extraction patients, which represent a challenge for conventional cardiac pacing. Methods: Between May 2014 and November 2021, 155 patients (120 males, 77.42%, mean age 78 ± 9 y) underwent M-TPS implantation in our Center, targeting a non-apical site of delivery when feasible. A subgroup of 48 patients (39 males, 81.25%) had undergone transvenous lead extraction. All patients fulfilled standard criteria for pacemaker implantation with specific indication to receive VVI pacing. The outcome evaluation included electrical performance (capture threshold, pacing impedance, R wave amplitude) before hospital discharge and then followed at 1, 6, and 12 months and then annually. Major complications were defined as life-threatening events, required surgical intervention or any event causing significant hemodynamic instability or resulting in death. High pacing threshold (HPT) was defined as 1.0 V/0.24 ms. Results: In 48/155 cases (39 males, 81, 25%) M-TPS was implanted after successful transvenous lead extraction. There were no statistically significant differences between groups for demographics characteristics, and PM implant indications. The implant procedure was successful in all cases and no device-related events were registered during follow-up. In particular, no device infection and/or malfunction were reported. Patients were followed-up for an average of 24 months (median 18 months). No differences were observed between groups in procedure duration, single device delivery (group 1 vs group 2: 63.21% vs 73.91%, p=0.20), fluoroscopy time (group 1 vs group 2: 11.79 ± 7.53 vs 10.49 ± 6.19 minutes, p=0.64), electrical performance at implant (group 1 vs group 2: pacing threshold 0.54 ± 0.35 V/0.24 ms vs 0.62 ± 0.32 V/0.24 ms, p=0.09; impedance 758.02 ± 227.89 Ohm vs 724.26 ± 178.14 Ohm, p=0.36; R wave amplitude 10.1 ± 4.73 mV vs 9.59 ± 5.30 mV, p=0.50) and at 18 month F-U (group 1 vs group 2: pacing threshold 0.50 ± 0.10 V/0.24 ms vs 0.85 ± 0.9 V/0.24 ms, p=0.45; impedance 559.58 ± 94.43 Ohm vs 543.34 ± 64.39 Ohm, p=0.69; R wave amplitude 12.00 ± 5.06 mV vs 13.42 ± 5.77 mV, p=0.55). Conclusions: Leadless pacemaker implant is a feasible, safe and effective option for patients treated with transvenous lead extraction, with electrical performance and outcomes comparable to a cohort of naïve patients at long-term follow up.